Adult Finns’ perceptions about communication with the dentist during their latest visit - Raittio E.; Lahti S.; Suominen A L. (Blackwell Munksgaard, 2022)
Objectives: The aim of this study was to investigate adult Finns’ perceptions about communication with the dentist during their latest visit in three aspects: receiving adequate information about health status and care, being listened to and shown interest by the dentist, and being able to influence the treatment decisions.
Methods: Data were taken from the Health 2011 Survey (BRIH8901). A representative sample (n = 5806) of adult Finns aged over 29 years old was interviewed or alternatively filled in a questionnaire. Basic descriptive tabulations, Rao‐Scott chi‐square tests and logistic regression analyses were used to study how socioeconomic status, perceived oral health and oral Health care variables are associated with the three aspects of communication with the dentist.
Results: Most (85%‐90%) adult Finns felt that, during their latest visit to a dentist, they had received adequate information, were listened to and shown interest by their dentist, and that they had been able to influence the treatment decisions. Those who perceived poor oral health, felt visiting dentist somewhat frightening, were in a difficult economic situation, visited a public dentist, or tended to visit oral Health care services irregularly, felt more often that there was a deficit in communication with the dentist.
Conclusions: In 2011, most adult Finns did not report any deficit in communication with the dentist during their latest visit. Oral Health care professionals should focus more on communicating with patients who have economic problems, poor oral health, dental fear or a problem‐oriented visiting pattern.